Observation of a near-threshold enhancement in the ?(?)over-bar mass spectrum from e+e- ? ??(?)over-bar at ?S is from 3.51 to 4.60 GeV - Ablikim, M.; Achasov, M. N.; Adlarson, P.; Ahmed, S.; Albrecht, M.; Aliberti, R.; Çetin, Serkant Ali (Amer Physical Soc, 2021)
The process e(+)e(-) -> phi Lambda(Lambda) over bar is studied using data samples collected with the BESIII detector at the BEPCII Collider at center of mass energies root S ranging from 3.51 GeV to 4.60 GeV. An enhancement is observed near the threshold of Lambda(Lambda) over bar. The lineshape of this enhancement is studied in different approaches, including fit with a Breit-Wiper function or a reversed exponential function. The Breit-Wigner function has a mass of (2262 +/- 4 +/- 28) McV/c(2) and a width of (72 +/- 5 +/- 43) MeV, where the quoted uncertainties are statistical and systematic, respectively. The rising rate of the reversed exponential function is measured as 33 +/- 11 +/- 6 MeV/c(2). For the Lambda(Lambda) over bar system, the J(PC) quantum numbers of 0(-+) and 0(+)(+) are rejected, while other J(PC) hypotheses are possible, according to the helicity-angle study. The energy-dependent cross section of the e(+)e(-) -> phi Lambda(Lambda) over bar process is measured for the first time in this energy region, and contributions from excited psi states and vector charmoniumlike Y-states are investigated.
Keywords: Monte-Carlo; Decay; Energies